2015
DOI: 10.1586/17512433.2015.1073587
|View full text |Cite
|
Sign up to set email alerts
|

Serelaxin a novel treatment for acute heart failure

Abstract: Acute heart failure (AHF) represents a major healthcare burden with a high risk of in-hospital and post-discharge mortality, which remained almost unchanged in the last few decades, underscoring the need of new treatments. Relaxin is a naturally occurring human peptide initially identified as a reproductive hormone and has been shown to play a key role in the maternal hemodynamic and renal adjustments that accommodate pregnancy. Recently, the new molecule serelaxin, a recombinant form of the naturally occurrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 63 publications
0
4
0
3
Order By: Relevance
“…Serelaxin reduces systemic vascular resistance and increases blood flow to the renal vessels, increasing cardiac output. Serelaxin is also known to participate in various cellular processes with antioxidative, anti-inflammatory, and antifibrotic actions 41). A recent large-scale clinical trial found that the intravenous injection of serelaxin for 48 hours at the initial stage of AHF caused rapid hemodynamic improvement, which ameliorated symptoms associated with pulmonary congestion and improved some clinical outcomes including 180-day mortality 42)43)44)45).…”
Section: Pharmacological Treatmentmentioning
confidence: 99%
“…Serelaxin reduces systemic vascular resistance and increases blood flow to the renal vessels, increasing cardiac output. Serelaxin is also known to participate in various cellular processes with antioxidative, anti-inflammatory, and antifibrotic actions 41). A recent large-scale clinical trial found that the intravenous injection of serelaxin for 48 hours at the initial stage of AHF caused rapid hemodynamic improvement, which ameliorated symptoms associated with pulmonary congestion and improved some clinical outcomes including 180-day mortality 42)43)44)45).…”
Section: Pharmacological Treatmentmentioning
confidence: 99%
“…Serelaxin is a recombinant form of human relaxin-2 with vasodilator properties; this new molecule has two G-protein coupled receptors (RXFP1 and RXFP2), activation of these receptors can result in triggering NO synthase, that appears to be central in the vascular modulation effects of serelaxin [100][101][102]. The RELAX-AHF trial randomized 1161 patients, admitted for acute heart failure, to receive standard care plus 48 hours intravenous infusion of placebo or serelaxin (30 µg/Kg per day) [103].…”
Section: Vasodilatorsmentioning
confidence: 99%
“…Chronic heart failure progression is modifiable using therapies that antagonize adverse neuro-hormonal pathways (beta-blockers, angiotensin-converting-enzyme inhibitors, angiotensin receptor blockers, and mineralocorticoid antagonists) while diuretics are effective in treating congestion and HF symptoms [ 41 , 42 ]. Despite the current improvement in the management of chronic heart failure, none of the available treatments has demonstrated to improve in prognosis in acute heart failure, except a new vasodilator whose trial is still underway [ 43 , 44 ] .…”
Section: Dietary Patterns In Cardiovascular Diseasementioning
confidence: 99%